The Effect of Achievement Motivation, Fear of Success on the Performance of Farming Women in Ngkaringkaring Village, Baubau City - hardin hardin; La Ode Muhammad Mustari; WODDP Sari (Institute for Research and Community Service, 2019)
The role of a woman is very important not only to take care of domestic life, but almost all activities in various sectors including farming, achievement motivation can lead a woman to succeed in living her life, but there is also within a woman the fear of success. This study aims: (1) To analyze the effect of achievement motivation on the performance of farmer women in Ngkaringkaring Village; (2) To analyze the effect of fear of success on the performance of women farmers in Ngkaringkaring Village; (3) To analyze the influence of achievement motivation and fear of success together on the performance of farmer women in Ngkaringkaring Village. This type of research is a quantitative study using multiple linear regression analysis The population of this study were all farm women who worked in the agricultural sector, amounting to 125 people. The sample of this study was 92 respondents. The results showed that the significant value for the variable of achievement motivation and fear of success on the performance of peasant women in the Seke Subak organization both partial and simultaneous tests gave a significant value smaller than 0.005, so there was an influence, but the fear of success had an influence and was marked negative. This is influenced by the dominance of the family of the peasant woman who requires not taking too long to take care of work outside the home.